Internet Operation of Aero Gas Turbines - Diakostefanis, Michail (Cranfield University, 2014)
Internet applications have been extended to various aspects of everyday life and offer services of high reliability and security. In the Academia, Internet applications offer useful tools for the remote creation of simulation models and real-time conduction of control experiments. The aim of this study was the design of a reliable, safe and secure software system for real time operation of a remote aero gas turbine, with the use of standard Internet technology at very low cost. The gas turbine used in this application was an AMT Netherlands Olympus micro gas turbine. The project presented three prototypes: operation from an adjacent computer station, operation within the Local Area Netwok (LAN) of Cranfield University and finally, remotely through the Internet. The gas turbine is a safety critical component, thus the project was driven by risk assessment at all the stages of the software process, which adhered to the Spiral Model. Elements of safety critical systems design were applied, with risk assessment present in every round of the software process. For the implementation, various software tools were used, with the majority to be open source API’s. LabVIEW with compatible hardware from National Instruments was used to interface the gas turbine with an adjacent computer work station. The main interaction has been established between the computer and the ECU of the engine, with additional instrumentation installed, wherever required. The Internet user interface web page implements AJAX technology in order to facilitate asynchronous update of the individual fields that present the indications of the operating gas turbine. The parameters of the gas turbine were acquired with high accuracy, with most attention given to the most critical indications, exhaust gas temperature (EGT) and rotational speed (RPM). These are provided to a designed real-time monitoring application, which automatically triggers actions when necessary. The acceptance validation was accomplished with a formal validation method – Model Checking. The final web application was inspired by the RESTful architecture and allows the user to operate the remote gas turbine through a standard browser, without requiring any additional downloading or local data processing. The web application was designed with provisions for generic applications. It can be configured to function with multiple different gas turbines and also integrated with external performance simulation or diagnostics Internet platforms. Also, an analytical proposal is presented, to integrate this application with the TURBOMATCH WebEngine web application, for gas turbine performance simulation, developed by Cranfield University.
Keywords: Asynchronous; AJAX; Remote; Real-time; Spiral; Safety Critical; Risk Assessment; Software Process; Formal Validation; Model Checking